Síntese e caracterização de novos derivados calix[4]areno-pirazina com potenciais propriedades luminescentes - Thiago Vinicius Costa Lara (2019)
Calixarenes are macrocyclic compounds characterized by the presence of a variable number of phenolic units joined by methylene bridges. Characteristics such as the possibility of obtaining large scale from low cost precursors, chemical and thermal stability and ease of functionalization, make the calixarenes versatile platforms for the development of a wide range of materials with potential applications in the biological and technological. Pyrazinic rings are known to have interesting photophysical properties, with potential applicabilities in sensors, organic light emitting diodes (OLEDs), liquid crystals and materials for non-linear optics. The capture property of ions and molecules by the calixarenes cavity allied to the potential luminescent property of the pyrazine ring is being studied by our research group. To this end, in this work three new calix derivatives [4] arenes functionalized with pyrazine rings in the upper rim were synthesized. Calix[4]arenes with pyrazine units 5, 9 and 14 are obtained in good yields, with their overall yields of 10%, 5% and 3%. In total, were synthesized five calixarenes never describe in literature, being the compounds, 5, 9, 12, 13 and 14.